Tingkat Kepuasan Remaja Surabaya terhadap Program Pagi Kanca Muda di Radio EBS FM Surabaya - Elma Gloria Pasaribu (LPPM Stikosa - AWS, 2018)
This study was conduct to examine how the level of satisfaction of Surabaya teenagers against program “Pagi Kanca Muda” on Radio EBS FM Surabaya. To find out how the level of satisfaction of Surabaya teenagers against program “Pagi Kanca Muda” on Radio EBS FM Surabaya, researcher is using Uses and Gratification Thory, the type of this study is descriptive quantitative research, the technique of collecting data in this study is using survey methods. From the data collected is analyzed in a descriptive to describe the satisfaction of Surabaya teenagers against program